The Key Roles of Mycobacterium tuberculosis FadD23 C-terminal Domain in Catalytic Mechanisms - Yan, Mengrong; Cao, Lin; Zhao, Li; Zhou, Weihong; Liu, Xiang; Zhang, Wei; Rao, Zihe (Frontiers in Microbiology, 2023)
Sulfolipid-1 (SL-1) is located in the Mycobacterium tuberculosis (M. tb) cell wall, and is essential for pathogen virulence and intracellular growth. Multiple proteins (e.g., Pks2, FadD23, PapA1, and MmpL8) in the SL-1 synthesis pathway can be used as drug targets, but, to date, their structures have not been solved. This study aimed to determine the crystal structures of FadD23 bound to ATP or hexadecanoyl adenylate. FadD23 is the first protein in the SL-1 synthesis pathway whose structure has been solved. We have also investigated long-chain saturated fatty acids as biological substrates of FadD23 through structural, biological, and chemical analyses. The mutation at the active site of FadD23 greatly influences enzymatic activity. Meanwhile, the FadD23 N-terminal domain alone cannot bind palmitic acid without C-terminal domain facilitation since it is almost inactive after removing the C-terminal domain. These results reveal the importance of the C-terminal domain in the catalytic mechanism.